The use of herbal medicine in children - Suryawati Suryawati; Hijra Novia Suardi (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
The herbal medicine has been widely used in children for the treatment of several symptoms and the prevention of diseases before accessing the hospital for professionals help. There are 3 kinds of marketed herbal medicine including empirical based herbal medicine (jamu), standardized herbal medicine (obat herbal terstandar) and clininically tested herbal medicine (fitofarmaka). This study aimed to investigate the utilization of the marketed herbal medicine along with non marketed ones which was known as the Indonesian original herbal medicine (Obat Asli Indonesia, OAI) in children. The cross sectional study was conducted by interviewing 91 parents whose children were hospitalized in RSUD Meuraxa, Banda Aceh. The interview was conducted using a structured questionnaire from 4 to 29 September 2014. The result showed that the Indonesian original herbal medicine was used most frequently followed by herbal (jamu), standardized herbal and clininically tested herbal medicine. The utilization of herbal medicine was associated with the knowledge of parents and did not correlate to their economic level. All of the parents did not know the side effects of herbal medicine to their children’s body and  few of them knew  the indication of herbal  remedies. Overall, it was  concluded  that eventhough the knowledge of parents about the safety and activity of herbal medicine was not sufficient the use of herbal medicine in children was common